Stay in the game: A randomized controlled trial of a sports and life skills program for vulnerable youth in Liberia - Beaman, Lori; Herskowitz, Sylvan; Keleher, Niall; Magruder, Jeremy (University of Chicago Press, 2021)
Over the past two decades, sports programs have proliferated as a mode of engaging youth in development projects. Thousands of organizations, millions of participants, and hundreds of millions of dollars are invested in sports-based development programs each year. The underlying belief that sports promote socioemotional skills, improve psychological well-being, and foster traits that boost labor force productivity has provided motivation to expand funding and offerings of sport for development (SFD) programs. We partnered with an international NGO to randomly assign 1200 young adults to a sports and life skills development program. While we do not see evidence of improved psychosocial outcomes or resilience, we do find evidence that the program caused a 0.12 standard deviation increase in labor force participation. Secondary analysis suggests that the effects are strongest among those likely to be most disadvantaged in the labor market.